2013
DOI: 10.1186/1746-1596-8-145
|View full text |Cite
|
Sign up to set email alerts
|

The expression of V-ATPase is associated with drug resistance and pathology of non-small-cell lung cancer

Abstract: ObjectiveThis article aims to investigate the expression of vacuolar-H + −ATPase (V-ATPase) in non-small cell lung cancer (NSCLC) and its variations with pathological type and grade. Furthermore, to evaluate the chemotherapy drug sensitivity of different cancer tissues as well as its correlation with V-ATPase expression in NSCLC.MethodsV-ATPase expression was examined in 92 NSCLC tissue samples using the immunohistochemical Envision method and immunofluorescence assay. The location of V-ATPase expression was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 31 publications
3
45
0
Order By: Relevance
“…Other studies have described expression of V‐ATPase/specific subunits in pancreatic cancer,32, 33 nonsmall cell lung cancer,34 oral squamous cell carcinoma,35, 36 ovarian cancer,37 cervical cancer,38 breast cancer,39, 40 gliomas,41 and hepatocellular carcinoma 42. A summary of studies investigating clinical significance of V‐ATPase in cancer is provided in Table 1.…”
Section: Dysregulation Of V‐atpase In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have described expression of V‐ATPase/specific subunits in pancreatic cancer,32, 33 nonsmall cell lung cancer,34 oral squamous cell carcinoma,35, 36 ovarian cancer,37 cervical cancer,38 breast cancer,39, 40 gliomas,41 and hepatocellular carcinoma 42. A summary of studies investigating clinical significance of V‐ATPase in cancer is provided in Table 1.…”
Section: Dysregulation Of V‐atpase In Cancermentioning
confidence: 99%
“…Increased cancer cell invasive activity is frequently associated with aberrant V‐ATPase plasma membrane localization suggesting that increased acidification of the extracellular space plays an important role 29, 33, 34, 37, 47, 48, 49, 50, 51, 52…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
“…It has been shown that metastatic phenotypes have higher expression of V-ATPase compared to NHE1 76 . Overexpression of V-ATPase is associated with a drug-resistant phenotype 77,78 . Weakly basic drugs such as doxorubicin are ionized extracellularly.…”
Section: Vacuolar Atpase (V-atpase)mentioning
confidence: 99%
“…In particular, it is overexpressed in NSCLC (Lu et al, 2013). Its expression is related to the pathological type and grade of cancer and is likely associated with chemotherapy drug resistance in NSCLC (Lu et al, 2013). Therefore, vATPase inhibitors may be promising cancer treatments.…”
Section: Introductionmentioning
confidence: 97%
“…vATPase is mainly involved in cancer metastasis and invasion (Gu and Gruenberg, 2000;Gocheva and Joyce, 2007). In particular, it is overexpressed in NSCLC (Lu et al, 2013). Its expression is related to the pathological type and grade of cancer and is likely associated with chemotherapy drug resistance in NSCLC (Lu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%